Carbon dioxide bubble-propelled microengines in carbonated water and beverages. Issue 45 (17th April 2018) - Zhang, Yan; Zhu, Hong; Qiu, Wenxuan; Zhou, Yilu; Huang, Gaoshan; Mei, Yongfeng; Solovev, Alexander A.
Abstract : We demonstrate a new type of gaseous fuel for rolled-up tubular Ti/Cr microengine powered by carbon dioxide microbubbles in carbonated water and brewed beverages. Abstract : We demonstrate a new type of gaseous fuel for rolled-up tubular Ti/Cr microengine powered by carbon dioxide microbubbles in carbonated water and brewed beverages. Existence of microbubble pockets is revealed using on-chip integrated transparent microtubes. Vertical position, angle of rotation and buoyancy of ferromagnetic Ti/Fe/Cr microengines are controlled using an external magnetic field.